PERAN PEMBERDAYAAN DAN KETERLIBATAN KERJA TERHADAP KEPUASAN KERJA DAN KINERJA: - - Marwan Marwan; Istib Saroh; Fadhliah M Alhadar; Jannati T (Jurnal Bisnis Terapan, 2020)
The aims of this study was to reveals the roles of empowerment and work involvement on job satisfaction and its impact on the performance of employees in the Ternate Agriculture Agency. The research designs were surveys and questionnaires. The population and sample in this study were the agricultural officials of Ternate City, totaling 135 employees, using the census method. Method of data analysis was Smart PLS 3.0. The results indicated that 1) empowerment have a positively and significantly effect on job satisfaction, 2) job involvement have positively and significantly effect on job satisfaction, 3) job satisfaction have a positively and significantly effect on employee performance, 4) empowerment have a positively and significantly effect on employee performance, 5) job involvement have a positively and significantly effect on performance, 6) job satisfaction mediated on the effect of empowerment on employee performance and 7) Job satisfaction mediated the effect of work involvement on employee performance. These results indicate that the problem of poor performance in the Ternate Agriculture Agency is closely related to the variables of empowerment, job involvement, and job satisfaction. One of the novelty this research is placement of job satisfaction as a mediation variables.